Studi Analisis Deskriptif Fenomena Ihtikar atas Penimbunan Minyak Goreng dan Konsekuensinya terhadap Pengambilan Hak Orang Miskin dalam Tinjauan Hadis - Aulia, Syahla Berta; Ridlo, Muhammad Abdurrasyid; NZ, Adriansyah (Jurnal Riset Agama, 2024)
The purpose of this research is to see the view of the hadisth about the law eliminating the rights of the poor in the case study of hoarding cooking oil. The study uses a qualitative method with a descriptive-analytic approach and a library research approach. The study discusses the law of hoarding cooking oil, which is rampant during the food crisis, which is resold at high prices and results in poor people being unable to buy of these staple foods. This study concludes that the taking of the rights of the poor in the case study of hoarding cooking oil is not allowed which can be equated with stealing, on the grounds that it is done secretly, is the right and property of another person and has evil intentions. However, the hoarding of cooking oil does not get the law of had (cut off the hand), but gets the law of ta’zir whose punishment is given by the competent authority by holding the principle of looking at the benefit of the people. Because, stolen goods are not stored in a special place like stolen goods in general.